Development and validation of method for analysis of favipiravir and remdesivir in volumetric absorptive microsampling with ultra high-performance liquid chromatography–tandem mass spectrophotometry - Harahap, Yahdiana; Noer, Roesytas Fitria; Simorangkir, Timbul Partogi H. (Frontiers in Medicine, 2023)
Favipiravir and remdesivir are drugs to treat COVID-19. This study aims to find an optimum and validated method for simultaneous analysis of favipiravir and remdesivir in Volumetric Absorptive Microsampling (VAMS) by Ultra High-Performance Liquid Chromatography Tandem Mass Spectrophotometry. The use of VAMS can be an advantage because the volume of blood is small and the sample preparation process is simple. Sample preparation was done by precipitation of protein using 500 µl of methanol. Analysis was carried out by ultra high-performance liquid chromatography tandem mass spectrophotometry with ESI+ and MRM with m/z 157.9 > 112.92 for favipiravir, 603.09 > 200.005 for remdesivir, and at m/z 225.968 > 151.991 for acyclovir as the internal standard. The separation was carried out using an Acquity UPLC BEH C18 column (100 x 2.1 mm; 1.7 m), 0.2% formic acid - acetonitrile (50:50), flow rate was 0.15 ml/min, and column temperature was 50oC. The analytical method has been validated with the requirements issued by the Food and Drug Administration (2018) and European Medicine Agency (2011). The calibration range of favipiravir is 0.5-160 µg/ml and 0.002-8 µg/ml for remdesivir.